Profiled steel sheet dry board system as an alternative construction system - Focusing on thermal comfort performance - Badaruzzaman W.H.W.; Azmi A.E.; Eng J.; Mohtar W.H.M.W. (School of Engineering and Technology, 2023)
Thermal comfort in buildings is a parameter needs to be looked into in countries particularly with tropical climate like Malaysia. Hot and humid weather increases temperature inside the house leading to low thermal comfort. Numerous modes of activities have been introduced to overcome this drawback, which includes introducing new construction materials. Thermal mass and energy-efficiency analysis conducted before this on a small-scale basis has compared few building materials used in Malaysia such as normal brick, plywood and an innovative panel system known as the Profiled Steel Sheet Dry Board (PSSDB) system. The test results showed that the PSSDB wall panel system could be considered as an alternative building material for the Malaysian climate. This study focuses on full-scale tests comparing the thermal performance between a PSSDB house and a conventional house. The purpose of this research is to study the internal temperature changes due to the ambient temperature for both types of houses. It is focusing on the temperature variation and behaviour of room and attic temperatures of both houses. Results showed that the PSSDB house offers better thermal comfort in its room and attic than conventional houses. 2006 by School of Engineering and Technology, Asian Institute of Technology.